Nitrification in a biofilm‐enhanced highly loaded aerated lagoon. (19th September 2019) - Patry, Bernard; Lessard, Paul; Vanrolleghem, Peter A.
Abstract: A full‐scale biofilm‐enhanced aerated lagoon using fixed submerged media was monitored using automated water quality monitoring stations over the span of one year to quantify its nitrification performance. The system was operating at a high organic loading rate averaging 5.8 g total CBOD5 /m 2 of media per day (23.9 g total CBOD5 /m 3 of lagoon per day), a total ammonia nitrogen loading rate averaging 0.9 g NH4 ‐N/m 2  day (3.7 g NH4 ‐N/m 3  day), and temperatures ranging from 1.6 to 20.8°C. The system showed an extended seasonal nitrification period compared with a simulated aerated lagoon system of the same dimensions. This extension of complete nitrification with approximately 1 month was observed in the fall despite the decrease of operating temperature down to 4°C. During this maximum nitrification period, substantial denitrification occurred, and the effluent un‐ionized ammonia ratio was reduced. A temporary loss of nitrification was also experienced in relation to an episode of elevated suspended solids concentration. Measured biofilm characteristics, namely the detachment dynamics and the biofilm thickness, were used to explain this temporary nitrification loss. During wintertime, a low nitrate production was still observed, suggesting year‐long retention of nitrifying bacteria in the biofilm. Practitioner points: Nitrification in a highly loaded biofilm‐enhanced aerated lagoon is mainly affected by operating temperature. Maximum nitrification is observed during the warmer months and occurs even at high organic loading rates (>5 g CBOD5 /m 2  day). Compared with a simulated suspended growth system, the biofilm‐enhanced lagoon shows a significantly extended nitrification period. The extension is observed at the end of the summertime maximum nitrification period. Low amounts of nitrate still produced during winter in the biofilm‐enhanced aerated lagoon suggest year‐long retention of autotrophic nitrifying biomass in the biofilm. Nitrification in the biofilm‐enhanced aerated lagoon is negatively impacted by the presence of important quantities of accumulated solids that resuspend when their digestion starts as temperature increases. Abstract : Nitrification performance and full‐scale viability of an highly loaded aerated lagoon enhanced with fixed submerged biofilm support media.